Fighting Racism through Teacher Union Democratization: Activist Educators in Social Justice Caucuses in New York City and Philadelphia - Asselin, Chloe (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
Since the election of Donald Trump as President of the United States in 2016, there has been a rise in reported hate crimes across the country. This study focuses on how educator activists in the Movement of Rank-and-File Educators (MORE), the social justice caucus of the United Federation of Teachers in New York City, and in the Caucus of Working Educators (WE), the social justice caucus of the Philadelphia Federation of Teachers, relate to fellow educators who express racist views. This study argues that when engaging with fellow educators, who have racist views, social justice caucus activists participate in practices, including building relationships, having difficult conversations, and engaging in collective protest activities, that deepen union presence at the workplace and increase participation in the union by creating cultures of solidarity (Fantasia, 1988). MORE and WE reaffirm the importance of labor organizing in the educational justice movement and of anti-racist activism in the labor movement. They fight oppression through practices that democratize their union, and at the same time, the focus on racial justice drives the need for greater union democracy because engaging with racial tensions requires a democratic space for members to fight dysconscious racism (King, 1997) and arrive at new understandings.